High 25-hydroxyvitamin D is associated with unexpectedly high plasma inflammatory markers in HIV patients on antiretroviral therapy. Issue 43 (October 2016) - Gangcuangco, Louie Mar A.; Kohorn, Lindsay B.; Chow, Dominic C.; Keating, Sheila M.; Norris, Philip J.; Nagamine, Lorna S.; Ndhlovu, Lishomwa C.; Souza, Scott A.; Kallianpur, Kalpana J.; Shikuma, Cecilia M.
Abstract : Abstract: Inflammation associated with low 25-hydroxyvitamin D (25(OH)D) is associated with increased morbidity and mortality among HIV-infected patients with vitamin D deficiency. We investigated the association between 25(OH)D and soluble biomarkers among HIV-infected patients on stable antiretroviral therapy. This is a cross-sectional study. This study focuses on assessment in subjects 40 years or older on stable antiretroviral therapy (ART) for >3 months. Chemiluminescent immunoassay was used to determine plasma 25(OH)D levels. Plasma soluble biomarkers were measured by Luminex technology. Multivariable linear regression analysis was used to assess the associations between log10 -25(OH)D and soluble biomarkers. Of 138 patients, median age was 50.5 (45, 57) years and 25(OH)D was 34.0 (25.0, 42.3) ng/mL. The majority were males (88%) and had undetectable HIV RNA (84.8%); 19 (13.8%) had 25(OH)D ≥50 ng/mL. Spline regression analyses suggested a J-shaped relationship between various plasma biomarkers and 25(OH)D. Among subjects with 25(OH)D ≥20 ng/mL, multivariable linear regression showed positive association between 25(OH)D and interleukin (IL)-10 (β = 1.84, P < 0.001), IL-6 (β = 0.72, P = 0.02), MPO (β = 0.47, P = 0.02), serum amyloid A (β = 1.20, P = 0.04), and tumor necrosis factor (TNF)-α (β = 0.51, P = 0.04). High 25(OH)D (≥50 ng/mL) was associated with higher IL-6 (β = 0.30, P = 0.009), IL-8 (β = 0.14, = 0.005), IL-10 (β = 0.43, P = 0.02), and TNF-α (β = 0.20, P = 0.04), independent of age, sex, ethnicity, body mass index, hepatitis C co-infection, current smoking status, CD4%, and HIV RNA. In older HIV-infected patients, high 25(OH)D was associated with higher (not lower) levels of proinflammatory cytokines. Higher-than-optimal 25(OH)D may be associated with immune dysregulation and may pose a potential health risk among HIV-infected patients.